2015
DOI: 10.1177/1071100715577371
|View full text |Cite
|
Sign up to set email alerts
|

Mid- to Long-term Clinical Outcome and Gait Biomechanics After Realignment Surgery in Asymmetric Ankle Osteoarthritis

Abstract: Level III, comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 83 publications
1
27
0
Order By: Relevance
“…Some authors reported a significant decrease of the TT 4,10,13,18,19 ; however, some did not. 1,12,14,27 Tanaka et al 27 reported that in all patients with a preoperative TT greater than 10 degrees, the joint space did not improve to normal.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some authors reported a significant decrease of the TT 4,10,13,18,19 ; however, some did not. 1,12,14,27 Tanaka et al 27 reported that in all patients with a preoperative TT greater than 10 degrees, the joint space did not improve to normal.…”
Section: Discussionmentioning
confidence: 96%
“…The talar tilt angle was completely corrected postoperatively (from 14.5 to 1.2 degrees), and the tibiocrural angle also was well corrected. ‡References 1,3,4,7,8,10,[12][13][14][15][18][19][20]24,26,27. …”
mentioning
confidence: 99%
“…The role of TT in SMOT is highly controversial. Some authors have reported a significant decrease of the TT [4, 7, 8, 11, 17]; however, others have not [3, 12, 15, 19]. Tanaka et al [12] reported that in all patients with a preoperative TT greater than 10°, the joint space did not return to normal.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that SMOT could restore the weight-bearing alignment of the ankle joint [35], decrease the contact pressure of the medial part of the tibiotalar joint [6], restore the congruence of the tibiotalar joint surface [5, 7, 8], improve the chondromalacia [9], postpone the OA progress [10], and even reverse the radiological ankle OA stages [2, 9, 11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…Supramalleolar osteotomy (SMOT) is an effective procedure for the treatment of midstage asymmetric ankle osteoarthritis [1][2][3][4]. Related studies have proved that the key factors affecting the postoperative curative effect of SMOT are the postoperative ankle Takakura stage [5], lower limb power line [6] and ankle angles [7]; but SMOT uses conventional operation (CO) method often does not perfectly accomplish these surgical aims leading to some patients have unsatisfactory outcomes [8,9].…”
Section: Introductionmentioning
confidence: 99%